A study on anxiety And depression level among high risk inpatient pregnant women in an obstetric ward - Raja Lexshimi RG,; Ho SE,; Hamidah Hassan,; Syed Zulkifli SZ,; Rohani M, (Penerbit UKM, 2007)
Pregnancy is perceived by many pregnant mothers as a period of happiness in anticipation of motherhood. Not all pregnant mothers experience cheerfulness as some may experience a high anxiety and depression level for unknown reasons. The purpose of this study was to determine the level of anxiety and depression among high risk pregnant women and the factors that contribute to their level of anxiety and depression. A descriptive cross-sectional study was conducted on 38 high risk mothers whose stay in hospital exceeded more than three days in the obstetric ward of Hospital Universiti Kebangsaan Malaysia. A self assessment questionnaire “Hospital Anxiety Depression scale” was used to measure the level of anxiety and depression among high risk pregnant women. Of the 38 participants, 16 (42.1%) women experienced a mild level of anxiety and 22 (57.9%) experienced a severe level of anxiety. Seventeen (44.7%) women was classified as having mild depression and 21 (55.3%) severe depression. The factors contributing to the level of anxiety and depression, include those related with “lack of information on disease”, “family matters” and “finance”. High risk pregnant women in this study experienced a significant level of anxiety and depression during their stay in hospital. It is therefore important for nurses and doctors to be aware and sensitive to the influencing factors that cause anxiety and depression as to enable high risk pregnant mothers to enjoy their pregnancy and childbirth